Teaching and Learning with Others: Situated Encounters in Service Learning among Pre-Service Teachers - Adarlo, Genejane M (Archīum Ateneo, 2020)
Service learning, as a pedagogical approach, can offer situated encounters or critical incidents for pre-service teachers to make sense of their professional identity in relation to others and the wider community. However, additional research is still needed to ascertain how teacher identity can arise from these situated encounters. Hence, this ethnographic case study looks at the emerging teacher identities of pre-service teachers by examining their service learning experiences in a literacy programme for pre-school children from an urban poor community in the Philippines. Specifically, constructs of teacher’s roles, understandings of the goals of education, sense of self-efficacy, and identification to the teaching profession are explored from their situated encounters in a literacy programme. The relevance of reflection and mentoring during the teaching-learning process of service learning is likewise considered. Thematic analysis of observation notes, submitted portfolios, and interview transcripts revealed how pre-service teachers can learn more about themselves and their pivotal role in society particularly when their service learning is deliberately oriented towards social justice. Such findings on these situated encounters in service learning can provide valuable insights as to how a social justice approach to service learning is important to curriculum design and implementation of teacher education.